2016
DOI: 10.1515/rjdnmd-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Glucose Disposal Rate (eGDR) – A Marker for the Assessment of Insulin Resistance in Type 1 Diabetes Mellitus

Abstract: Background and Aims: Studies have shown an increased incidence of chronic complications in people with type 1 diabetes mellitus (T1DM) with insulin resistance (IR) compared to people with T1DM without IR. Estimated glucose disposal rate (eGDR) is an important indicator of IR in patients with T1DM, lower eGDR levels indicating greater IR. It was shown that T1DM patients with chronic complications (diabetic retinopathy - DR, diabetic peripheral neuropathy - DPN or diabetic kidney disease - DKD) exhibit higher IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…In this study, patients who had low eGDR had higher weight SDS, BMI SDS and waist / hip ratio. This was similar to study conducted by Mihaela L. Bîcu et al who found that obese patients had lower eGDR in comparison with lean subjects (19). Higher insulin doses and an increase in the rate of hypoglycemia may be possible causes for development of obesity and subsequent insulin resistance in T1DM cases (20).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, patients who had low eGDR had higher weight SDS, BMI SDS and waist / hip ratio. This was similar to study conducted by Mihaela L. Bîcu et al who found that obese patients had lower eGDR in comparison with lean subjects (19). Higher insulin doses and an increase in the rate of hypoglycemia may be possible causes for development of obesity and subsequent insulin resistance in T1DM cases (20).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, negative CVD outcomes were also related to longer diabetes duration and lower HbA1c. Bicu et al [13] also found that eGDR was strongly negatively correlated with CVD events in patients with T1D and diabetes duration longer than 10 years. Interesting, that lower HbA1c had a negative effect on CVD outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…Better knowledge of factors controlling IR in T1D is important not least because of strong evidence for the relationship between IR and cardiovascular disease (CVD) [4,8,9]. Several studies [10][11][12][13] have also shown a clear association between IR and an increased incidence of chronic complications in people with T1DM.…”
Section: Key Summary Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with T1D, the estimated glucose disposal rate (eGDR) has been proven to be a key indicator of IR, with decreased eGDR levels suggesting IR [7].…”
Section: Introductionmentioning
confidence: 99%